Binder for silicon nitride tape-casting green body, silicon nitride tape-casting green body, preparation method of silicon nitride tape-casting green body, ceramic wafer and application of ceramic wafer
By using a combination of polymer and low molecular weight binder in the casting process of silicon nitride ceramic sheets, the density unevenness and cracking problems caused by poor binder dispersion are solved, and the uniform dispersion and smooth surface of the ceramic sheets are achieved, and the yield of finished products is improved.
Patent Information
- Application Number
- CN202410930981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the silicon nitride ceramic sheet cannot be well dispersed during casting, resulting in problems such as powder particles settling and glue migration, resulting in uneven density and embryo cracking.
A combination of adhesives including polymer binders and low-molecular binders is adopted. The interaction between polymer binders and powders increases embryogenesis strength, and low-molecular binders improve dispersion, avoiding cracking caused by stress concentration during glue discharge.
The raw materials for casting embryos in silicon nitride are uniformly dispersed, and the surface of casting embryos is flat and cracked, which improves the finished product yield of silicon nitride ceramic sheets.
Smart Images

Figure CN119751092A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a binder for silicon nitride tape-casting embryos, a silicon nitride tape-casting embryo and a preparation method thereof, and a ceramic sheet and application thereof. Background Art
[0002] In the related art, the slurry is prepared by mixing silicon nitride powder, sintering aids, etc. in a ball mill; the slurry is tape-casted, degreased, and sintered to obtain the finished silicon nitride ceramic sheet. However, during the ball milling process, the binder itself is prone to clumping and core wrapping and cannot be well dispersed, or the powder cannot be well wrapped due to factors such as degree of polymerization and hydroxyl content, resulting in powder particle sedimentation and glue migration during the tape casting process, resulting in uneven density and cracking of the green embryo. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a binder for silicon nitride tape casting embryos, so that the raw materials of the silicon nitride tape casting embryos are evenly dispersed and the surface of the tape casting embryos is flat and free of cracks.
[0004] Another object of the present invention is to provide a silicon nitride tape casting green body.
[0005] Another object of the present invention is to provide a method for preparing a silicon nitride tape-casting embryo.
[0006] Another object of the present invention is to provide a ceramic sheet.
[0007] Another object of the present invention is to provide an application of a ceramic sheet.
[0008] According to an embodiment of the first aspect of the present invention, the present invention provides a binder for silicon nitride tape casting embryos, comprising: a first binder and a second binder, wherein the weight average molecular weight of the first binder satisfies: (120-250)×10 3 The weight average molecular weight of the second binder satisfies: (25-90)×10 3 ; The weight ratio of the first binder to the second binder is 1:1 to 2.5.
[0009] According to the binder for silicon nitride tape casting embryos of the present invention, the binder includes two or more different molecular weights in combination, the first binder (i.e., polymer binder) can interact with more powders to improve the embryo strength, and decompose and volatilize at a higher temperature; the second binder (i.e., low molecular binder) can improve the dispersibility, and decompose and volatilize at a lower temperature; the two are mixed, on the one hand, can improve the slurry stability, on the other hand, avoid the cracking phenomenon caused by stress concentration during the debinding process. Thereby, the yield rate of the finished silicon nitride tape casting embryos can be improved.
[0010] According to some embodiments of the present invention, the hydroxyl content in the first binder is 17.5% to 20%; the hydroxyl content in the second binder is 11% to 23%.
[0011] According to some embodiments of the present invention, the first binder and / or the second binder is polyvinyl butyral.
[0012] According to an embodiment of the second aspect of the present invention, the present invention provides a silicon nitride tape casting green body, which comprises, by mass percentage: 45% to 55% of silicon nitride powder, 1% to 3% of sintering aid, 0.5% to 3% of dispersant, 4% to 8% of binder, 2.5% to 8% of plasticizer, 0.2% to 0.5% of defoamer and 25% to 45% of organic solvent; Wherein, the adhesive is the adhesive for silicon nitride tape casting green body described in the embodiment of the first aspect.
[0013] According to some embodiments of the present invention, the silicon nitride powder includes an α phase and a β phase, wherein the content of the α phase is w in mass percentage, wherein w satisfies: w>90%.
[0014] According to some embodiments of the present invention, the grain size of the silicon nitride powder satisfies: D50<1um; and / or, The specific surface area of the silicon nitride powder is m, wherein m satisfies: 10m 2 / g≤m≤20m 2 / g.
[0015] According to some embodiments of the present invention, the sintering aid comprises magnesium oxide and / or yttrium oxide; and / or, The grain size of the sintering aid satisfies: D50<2um.
[0016] According to some embodiments of the present invention, the dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil.
[0017] According to some embodiments of the present invention, the organic solvent is a binary solvent system of a first organic solvent and a second organic solvent, and the weight ratio of the first organic solvent to the second organic solvent satisfies: 4:6 to 7:3; Preferably, the first organic solvent is ethanol, and the second organic solvent is ethyl acetate and / or butyl acetate.
[0018] According to some embodiments of the present invention, the plasticizer includes at least one of dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, polyethylene glycol and triethylene glycol diisooctanoate.
[0019] According to some embodiments of the present invention, the defoaming agent includes at least one of a polyether defoaming agent, a silicone defoaming agent and a silicon-free defoaming agent.
[0020] According to an embodiment of the third aspect of the present invention, the present invention provides a method for preparing a silicon nitride tape-casting embryo, comprising: Prepare slurry: weigh 45% to 55% of silicon nitride powder, 1% to 3% of sintering aid, 0.5% to 3% of dispersant and 10% to 20% of organic solvent based on the mass percentage of each component in the slurry, mix them to obtain slurry; Preparation of sol: Based on the mass percentage of each component in the sol, weigh 4% to 8% of a binder, 2.5% to 8% of a plasticizer, 0.2% to 0.5% of a defoamer and 15% to 25% of an organic solvent, stir and mix to obtain a sol; Preparing silicon nitride tape casting slurry: mixing the sol and the slurry to prepare silicon nitride tape casting slurry; Tape casting: The silicon nitride tape casting slurry is tape cast to obtain a silicon nitride tape casting green body.
[0021] According to some embodiments of the present invention, the step of preparing the slurry comprises: fully mixing the components by ball milling, wherein the mixing temperature is 20°C to 30°C, the mixing speed is 200rpm to 300rpm, the mixing method is ball milling, and the ball milling time is 10h to 24h; and / or, Preparation of sol step: controlling the stirring temperature to 20°C to 30°C, the stirring speed to 200rpm to 400rpm, and the stirring time to 2h to 5h; and / or, The steps of preparing silicon nitride tape casting slurry are as follows: the temperature of the tape casting is 20° C. to 30° C., the speed of the tape casting is 200 rpm to 300 rpm, and the time of the tape casting is 10 h to 24 h; Tape casting steps: set the scraper height to 1.0 mm to 1.5 mm, the tape casting speed to 50 mm / min to 100 mm / min, and the drying temperature to 40° C. to 55° C.; finally, a silicon nitride tape casting green body with a thickness of 0.40 mm to 0.65 mm is obtained.
[0022] According to an embodiment of the fourth aspect of the present invention, the present invention provides a ceramic sheet, which is made by sintering the silicon nitride tape-cast green body described in the embodiment of the first aspect of the present invention, or by sintering the silicon nitride tape-cast green body prepared by the preparation method described in the embodiment of the second aspect of the present invention.
[0023] According to an embodiment of a fifth aspect of the present invention, the present invention provides an application of a ceramic sheet according to an embodiment of a fourth aspect of the present invention, wherein the ceramic sheet is applied to a substrate material of a power device.
[0024] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a picture of a silicon nitride tape-cast green body according to Example 1 of the present invention; Figure 2 is a picture of a silicon nitride tape-cast green body according to Example 2 of the present invention; Figure 3 is a picture of a silicon nitride tape-cast green body according to Comparative Example 1 of the present invention; Figure 4 is a picture of a silicon nitride tape-casting embryo according to Comparative Example 2 of the present invention; Figure 5 is a picture of a silicon nitride tape-cast green body according to Comparative Example 3 of the present invention; Figure 6 It is a schematic diagram of the preparation process of the adhesive according to a specific embodiment of the present invention. DETAILED DESCRIPTION
[0026] The binder for silicon nitride tape casting green body according to the first embodiment of the present invention is described in detail below.
[0027] According to the first embodiment of the present invention, the binder for silicon nitride tape casting embryo comprises: a first binder and a second binder, and the weight average molecular weight of the first binder satisfies: (120-250)×10 3 The weight average molecular weight of the second binder satisfies: (25-90)×10 3. In this way, the binder is a combination of two or more different molecular weights. The first binder (polymer binder) is more likely to form physical entanglement points to form a three-dimensional network structure, thereby effectively preventing particle sedimentation and improving system stability. Therefore, it can interact with more powders to improve the strength of the green embryo, but due to its poor solubility and high viscosity, it requires more solvent supplementation when used alone, is prone to cracking during drying and molding, and decomposes and volatilizes at higher temperatures; the second binder (low molecular binder) can be evenly dispersed between the systems and is easier to enter the gaps between the green embryos. After debinding, the pores are relatively small, which is conducive to sintering densification and can improve dispersibility. However, due to the short molecular chain, the addition amount is high and the system stability is poor, and it decomposes and volatilizes at a lower temperature. The two are mixed. By using binders of different molecular weights in combination, the stability and viscosity of the system can be taken into account at a relatively small addition amount, which is suitable for tape casting. In addition, since the debinding temperature increases with the increase of the molecular weight of the adhesive, by compounding adhesives with different molecular weights, the cracking of the ceramic sheet caused by stress concentration during the degreasing and debinding process can be effectively avoided, thereby improving the yield of the finished product. In this way, the binder for silicon nitride tape casting embryos of the present invention can improve the slurry stability on the one hand, and avoid the cracking caused by stress concentration during the debinding process on the other hand.
[0028] Among them, the weight ratio of the first binder to the second binder is 1:1 to 2.5. Further, if the weight ratio is greater than 1:1, the content of the low molecular binder is relatively small, the viscosity of the system increases, the binder cannot be fully stretched, and the powder dispersion performance is reduced. If the weight ratio is less than 1:2.5, the content of the polymer binder is relatively small, and the strength of the silicon nitride tape-cast embryo may be low. By setting the weight ratio of the polymer binder to the low molecular binder to 1:1 to 2.5, the silicon nitride slurry has good stability and the strength of the silicon nitride tape-cast embryo is high.
[0029] According to the specific embodiment of the present invention, the silicon nitride tape casting embryo is a combination of two or more adhesives with different molecular weights. The high molecular adhesive can interact with more powders to improve the embryo strength, and decompose and volatilize at a higher temperature; the low molecular adhesive can improve the dispersibility, and decompose and volatilize at a lower temperature; the two are mixed, on the one hand, to improve the slurry stability, and on the other hand, to avoid the cracking phenomenon caused by stress concentration during the debinding process. Thereby, the yield rate of the finished silicon nitride tape casting embryo can be improved.
[0030] According to some embodiments of the present invention, the hydroxyl content in the first binder is 17.5% to 20%; the hydroxyl content in the second binder is 11% to 23%. In this way, when the hydroxyl content in the first binder and / or the second binder is high, the polarity of the binder is large and the solubility in polar solvents is high. Controlling the hydroxyl content is to control the polarity to match the solvent. In addition, the increase in the hydroxyl content increases the viscosity of the binder, thereby increasing the viscosity of the slurry, making tape casting difficult, and increasing the hygroscopicity, so that the risk of sintering cracking when forming ceramic sheets is reduced; if the hydroxyl content is too low, the strength of the green film is low, and cracking occurs during the molding process. By limiting the hydroxyl content in the first binder and the second binder, the system stability and viscosity of the slurry can be better balanced, making the slurry suitable for tape casting.
[0031] According to some embodiments of the present invention, the first binder and / or the second binder is polyvinyl butyral. Here, the purity of polyvinyl butyral in polyvinyl butyral (PVB resin) is greater than 97.5%; the water content is less than 2.5%; the weight average molecular weight of the low molecular weight polyvinyl butyral is (25-90)×10 3 The hydroxyl content is 11% to 23%, preferably 17.5% to 20%; the weight average molecular weight of the high molecular weight polyvinyl butyral is (120 to 250)×10 3 , the hydroxyl content is 17.5% to 21%; wherein the ratio of high molecular weight PVB to low molecular weight PVB is 1:(1 to 2.5). Figure 6As shown, PVB resin is obtained by reacting polyvinyl alcohol (PVA) with butyraldehyde under the action of a catalyst. Since polyvinyl alcohol has the characteristics of multiple hydroxyls, it is impossible to carry out 100% acetalization reaction, so PVB can be a copolymer of PVB, PVAc, and PVA. In the first adhesive and / or the second adhesive, as the hydroxyl content (PVA component) increases, the strength of the generated silicon nitride cast embryo film increases, the system stability is improved, but the viscosity of the slurry increases. Specifically, it is easier to form physical entanglement points between high molecular weight PVB chains to form a three-dimensional network structure, thereby effectively preventing particle sedimentation and improving system stability. However, due to the poor solubility and high viscosity of high molecular weight PVB, more solvent supplement is required when used alone, and cracking is prone to occur during drying and molding. Low molecular weight PVB chains can be evenly dispersed between the systems and are more likely to enter the gaps between the embryos. After debinding, the pores are relatively small, which is conducive to sintering densification, but due to the short molecular chain of low molecular weight PVB, the addition amount is high and the system stability is poor. By using polyvinyl butyral with different molecular weights, the stability and viscosity of the silicon nitride tape green body system can be controlled under the condition of adding a small amount of adhesive, which is suitable for tape casting. In addition, since the debinding temperature increases with the increase of PVB molecular weight, by using PVB with different molecular weights for compounding, the cracking of silicon nitride tape green body caused by stress concentration during degreasing and debinding can be effectively avoided, and the yield of silicon nitride tape green body finished products can be improved. Among them, the adhesive can be purchased or prepared as needed. The first adhesive can be B72 (molecular weight 170K~250K, hydroxyl content 17.5%~20%), B74 (molecular weight 120K~150K, hydroxyl content 17.5%~20%) purchased from Eastman, or B6OH (molecular weight 150K~170K, hydroxyl content 18%~21%) purchased from Kuraray, etc. The second adhesive can be B79 (molecular weight 50K~80K, hydroxyl content 11%~13%), B90 (molecular weight 70K~100K, hydroxyl content 18.5%~20.5%), B98 (molecular weight 40K~70K, hydroxyl content 18%~20%) purchased from Eastman, or B3OH (molecular weight 60K~90K, hydroxyl content 18%~21%) purchased from Kuraray, etc., but are not limited thereto.
[0032] According to an embodiment of the second aspect of the present invention, the present invention provides a silicon nitride tape casting embryo, which includes, by mass percentage: 45% to 55% silicon nitride powder, 1% to 3% sintering aid, 0.5% to 3% dispersant, 4% to 8% binder, 2.5% to 8% plasticizer, 0.2% to 0.5% defoamer and 25% to 45% organic solvent. In this way, the binder, plasticizer, defoamer and organic solvent are fully mixed to promote the dispersion of the silicon nitride tape casting slurry, thereby improving the yield of the finished silicon nitride tape casting embryo.
[0033] The binder is a binder for silicon nitride tape casting embryos according to the first embodiment. In this way, the binder is a combination of two or more different molecular weights. The high molecular binder can interact with more powders to improve the embryo strength and decompose and volatilize at a higher temperature; the low molecular binder can improve the dispersibility and decompose and volatilize at a lower temperature; the two are mixed, which can improve the slurry stability on the one hand and avoid cracking caused by stress concentration during the debinding process on the other.
[0034] According to the specific embodiment of the present invention, the silicon nitride tape casting embryo is a combination of two or more adhesives with different molecular weights. The high molecular adhesive can interact with more powders to improve the embryo strength, and decompose and volatilize at a higher temperature; the low molecular adhesive B98 can improve the dispersibility, and decompose and volatilize at a lower temperature; the two are mixed, on the one hand, to improve the slurry stability, and on the other hand, to avoid the cracking phenomenon caused by stress concentration during the debinding process. Thereby, the yield rate of the finished silicon nitride tape casting embryo can be improved.
[0035] According to some embodiments of the present invention, the silicon nitride powder includes an α phase and a β phase, wherein the content of the α phase is w in mass percentage, wherein w satisfies: w>90%. This arrangement is such that during the sintering process of the silicon nitride tape casting green body preparation process, sufficient α phase melts and undergoes phase change, promoting sintering densification and promoting the silicon nitride tape casting green body to form a flat surface.
[0036] According to some embodiments of the present invention, the grain size of the silicon nitride powder satisfies: D50<1 um. In this way, the grain size of the silicon nitride powder is small and easy to disperse.
[0037] According to some embodiments of the present invention, the specific surface area of silicon nitride powder is m, where m satisfies: 10m 2 / g≤m≤20m 2 / g. If m is less than 10m 2 / g, the specific surface area of silicon nitride powder is small, the grain size of silicon nitride powder is large, and sintering densification is difficult. If m is greater than 20m 2 / g, the specific surface area of silicon nitride powder is large, the grain size of silicon nitride powder is small, and it may be easy to agglomerate. By setting, m satisfies 10m 2 / g≤m≤20m 2 / g, the specific surface area of silicon nitride powder is appropriate, the grain size of silicon nitride powder is appropriate, the specific surface area is appropriate, the dispersion is good, and it is not easy to agglomerate, so that the raw materials of silicon nitride tape casting embryo are evenly dispersed, and the surface of the tape casting embryo is flat and crack-free. Thereby improving the finished product yield of ceramic sheets.
[0038] According to some embodiments of the present invention, in the silicon nitride powder, the impurity atomic content of Fe, Al, Ca is less than 300ppm; the C atomic content is less than 0.1wt%, and the oxygen content is less than 1wt%. Such a setting of the silicon nitride powder has a high purity, which is conducive to forming a silicon nitride tape casting embryo with excellent performance. For example, the bending strength and thermal conductivity of the silicon nitride tape casting embryo can be improved.
[0039] According to some embodiments of the present invention, the sintering aid includes magnesium oxide and / or yttrium oxide. In this way, yttrium oxide and magnesium quartz can form a liquid phase or a limited substitution solid solution at a lower temperature, and when sintering to form a ceramic sheet, the density of the sintered sample can be improved. Among them, magnesium oxide, yttrium oxide: purity> 99.5%; heteroatom content Fe, Al, Ca<300ppm; moisture<0.1wt%.
[0040] According to some embodiments of the present invention, the grain size of the sintering aid satisfies: D50<2um. In this way, the grain size of the sintering aid is small and easy to disperse in the silicon nitride tape casting green body.
[0041] According to some embodiments of the present invention, the dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil. The dispersant can wet and disperse the silicon nitride powder, prevent particle agglomeration, and reduce the viscosity of the slurry. At least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil is used as a dispersant, which has good compatibility with raw materials such as organic solvents and promotes the dispersion of the raw materials.
[0042] According to some embodiments of the present invention, the organic solvent is a first organic solvent-second organic solvent binary solvent system, and the first organic solvent: the second organic solvent satisfies the ratio of 4:6 to 7:3 by weight. In this way, the first organic solvent-second organic solvent binary solvent system has sufficient solubility for the PVB binder to adjust the solubility of PVB with different molecular weights / hydroxyl contents and adjust the viscosity of the slurry. When the first organic solvent: the second organic solvent satisfies the ratio of 4:6 to 7:3 by weight, the binary solvent system has better solubility for the PVB binder.
[0043] The solvent used this time is an ethanol-ethyl acetate binary solvent system, and the ratio is adjusted to (4:6, 5:5, 6:4 or 7:3) according to the solubility of the PVB adhesive. Compared with the traditional benzene / ketone solvent system, this formula is environmentally friendly and inexpensive.
[0044] According to some embodiments of the present invention, the first organic solvent is ethanol, and the second organic solvent is ethyl acetate and / or butyl acetate. In this way, the ethanol-ethyl acetate binary solvent system can be used to adjust the ratio according to the solubility of the PVB adhesive, and the solubility of the PVB adhesive is good. Compared with the traditional solvent system, this formula is environmentally friendly and low in price.
[0045] According to some embodiments of the present invention, the plasticizer includes at least one of dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, polyethylene glycol and triethylene glycol diisooctanoate. In this way, the toughness of the silicon nitride tape-casting embryo can be adjusted by adding the above plasticizer.
[0046] According to some embodiments of the present invention, the defoamer includes at least one of a polyether defoamer, a silicone defoamer and a silicone-free defoamer. In this way, the defoamer is widely available and cheap.
[0047] According to an embodiment of the third aspect of the present invention, the present invention provides a method for preparing a silicon nitride tape-casting embryo, comprising: Prepare slurry: weigh 45% to 55% of silicon nitride powder, 1% to 3% of sintering aid, 0.5% to 3% of dispersant and 10% to 20% of organic solvent based on the mass percentage of each component in the slurry, mix them to obtain slurry; Preparation of sol: Based on the mass percentage of each component in the sol, weigh 4% to 8% of the binder, 2.5% to 8% of the plasticizer, 0.2% to 0.5% of the defoamer and 15% to 25% of the organic solvent, and stir and mix to obtain a sol. The binder is evenly distributed in the solvent in advance to effectively prevent the occurrence of agglomeration and improve the yield of tape casting. Specifically, the binder, plasticizer, defoamer and organic solvent are formed into a sol to prevent the binder from agglomerating or wrapping during the preparation of the silicon nitride tape casting embryo. If the binder agglomerates or wraps, the silicon nitride tape casting slurry will not be easily dispersed, which will lead to cracking, depression or agglomeration of the silicon nitride tape casting embryo.
[0048] Preparing silicon nitride tape casting slurry: mixing the sol and the slurry to prepare the silicon nitride tape casting slurry; Tape casting is to tape cast the silicon nitride tape casting slurry to obtain the silicon nitride tape casting embryo. In the tape casting process, a binder (such as PVB) is required to form a long chain structure in the solvent and distribute it throughout the slurry system. The silicon nitride powder is wrapped by these long chains, and the powder is supported and dispersed by steric hindrance or steric stabilization mechanism.
[0049] According to the preparation method of a specific embodiment of the present invention, the binder, plasticizer, defoamer and solvent are first stirred and mixed at high speed to prepare a presol, so as to prevent the binder itself from clumping and core-wrapping during the ball milling process, which may cause cracking and defects of the green embryo and fail to disperse well, thereby further improving the yield of the finished product.
[0050] According to some embodiments of the present invention, the slurry preparation step is: the components are fully mixed by ball milling, the mixing temperature is 20°C to 30°C, the mixing speed is 200rpm to 300rpm, the mixing method is ball milling, and the ball milling time is 10h to 24h. In this way, the temperature, speed and ball milling time of the ball mill are controlled to ensure that a uniformly mixed slurry is obtained.
[0051] According to some embodiments of the present invention, the steps of preparing the sol are as follows: stirring temperature: 20°C to 30°C, stirring speed: 200rpm to 400rpm, stirring time: 2h to 5h. In this way, the stirring temperature, stirring and stirring time are controlled to ensure that the raw materials are uniformly mixed to obtain the sol. Optionally, stirring is performed using a high-speed stirrer.
[0052] According to some embodiments of the present invention, the steps of preparing silicon nitride tape casting slurry are as follows: the temperature of tape casting is 20°C to 30°C, the speed of tape casting is 200rpm to 300rpm, and the time of tape casting is 10h to 24h. In this way, the temperature, speed and grinding time of tape casting are controlled to ensure that a uniformly mixed silicon nitride tape casting slurry is obtained.
[0053] Tape casting steps: set the scraper height to 1.0 mm to 1.5 mm, the casting speed to 50 mm / min to 100 mm / min, and the drying temperature to 40°C to 55°C; finally, a silicon nitride tape casting embryo with a thickness of 0.40 mm to 0.65 mm is obtained. After vacuum degassing of the silicon nitride tape casting slurry, pour it into the tape casting tank, set the scraper height, casting speed, and drying temperature. Thus, a silicon nitride tape casting embryo with a thickness of 0.40 to 0.65 mm is obtained.
[0054] According to an embodiment of the fourth aspect of the present invention, the present invention provides a ceramic sheet, which is made by sintering the silicon nitride tape-cast green body according to the embodiment of the second aspect of the present invention, or by sintering the silicon nitride tape-cast green body prepared by the preparation method according to the embodiment of the third aspect of the present invention.
[0055] The ceramic sheet according to the embodiment of the fourth aspect of the present invention has good sintering formability and high yield.
[0056] According to an embodiment of a fifth aspect of the present invention, the present invention provides an application of a ceramic sheet according to an embodiment of a fourth aspect of the present invention, where the ceramic sheet is applied to a substrate material of a power device.
[0057] When the ceramic sheet according to the specific embodiment of the present invention is applied to the substrate material of a power device, the substrate material of the power device has a high molding yield and good surface performance.
[0058] The silicon nitride tape-casting green body of the present invention is further described below through specific exemplary embodiments and comparative examples and performance tests of the obtained silicon nitride tape-casting green body.
[0059] Example 1 (compounded PVB adhesive + presol) A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 46 wt % silicon nitride powder, 1.5 wt % magnesium oxide, 1 wt % yttrium oxide, 1 wt % triethyl phosphate, 12.5 wt % ethanol and 5 wt % ethyl acetate were ball-milled at 300 rpm for 12 h at 25 ° C to prepare a slurry; 3.75wt% of a first adhesive B72 (purchased from Eastman, molecular weight 170-250K, hydroxyl content 17.5%-20%) and 3.75wt% of a second adhesive B98 (purchased from Eastman, molecular weight 40K-70K, hydroxyl content 18%-20%), 3.75wt% of polyethylene glycol 600, 3.75wt% of dibutyl phthalate, 0.5wt% of BYK-1790 defoamer, 13wt% of ethanol and 5.5wt% of ethyl acetate were stirred in a high-speed stirrer at 25°C and 300rpm for 2h to prepare a sol; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, pour the silicon nitride casting slurry C into the casting tank, set the scraper height to 1.5 mm, casting speed to 50 mm / min, and drying temperature to 40°C; finally, obtain the silicon nitride casting green embryo. Figure 1 shown.
[0060] Example 2 (compounded PVB adhesive + presol) A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 48.5wt% silicon nitride powder, 1.5wt% magnesium oxide, 1wt% yttrium oxide, 1wt% polyvinyl pyrrolidone, 13wt% ethanol and 5.5wt% ethyl acetate were ball-milled at 25°C and 300rpm for 12h to prepare a slurry; 2wt% B72 and 4.5wt% B98, 4wt% triethylene glycol diisooctanoate, 0.5wt% BYK-1790 defoamer, 13wt% ethanol and 5.5wt% ethyl acetate were stirred in a high-speed stirrer at 25°C and 300rpm for 2h to prepare a sol; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, pour the silicon nitride casting slurry C into the casting tank, set the scraper height to 1.5 mm, casting speed to 50 mm / min, and drying temperature to 55°C; finally, obtain the silicon nitride casting green embryo. Figure 1 shown.
[0061] Example 3 A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 45wt% silicon nitride powder, 0.5wt% magnesium oxide, 0.5wt% yttrium oxide, 1wt% castor oil, and 20wt% organic solvent (ethanol:ethyl acetate=7:3) were ball-milled at 300rpm for 12h at 25°C to prepare a slurry; 4wt% binder (B72: B90 = 1: 1), 2.5wt% triethylene glycol diisooctanoate, 0.5wt% BYK-1790 defoamer, and 25wt% organic solvent (ethanol: ethyl acetate = 7: 3) were stirred in a high-speed mixer at 25°C and 300rpm for 2h to prepare a sol; wherein B90 was purchased from Eastman, with a molecular weight of 70K-100K and a hydroxyl content of 18.5%-20.5%; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, the silicon nitride casting slurry C was poured into the casting tank, and the scraper height was set to 1.5 mm, the casting speed was 50 mm / min, and the drying temperature was 45° C. Finally, the silicon nitride casting green body was obtained.
[0062] Example 4 A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 55wt% silicon nitride powder, 1.3wt% magnesium oxide, 0.7wt% yttrium oxide, 0.5wt% polyvinyl pyrrolidone, and 16wt% organic solvent (ethanol: ethyl acetate = 7:3) were ball-milled at 300rpm for 12h at 25°C to prepare a slurry; 6wt% binder (B72:B90=1:2.5), 5.15wt% plasticizer (dibutyl phthalate:PEG600=1:1), 0.35wt% BYK-1790 defoamer, and 15wt% organic solvent (ethanol:ethyl acetate=7:3) were stirred in a high-speed stirrer at 25°C and 300rpm for 2h to prepare a sol; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, the silicon nitride casting slurry C was poured into the casting tank, and the scraper height was set to 1.5 mm, the casting speed was 50 mm / min, and the drying temperature was 40° C. Finally, the silicon nitride casting green body was obtained.
[0063] Example 5 A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 50wt% silicon nitride powder, 2wt% magnesium oxide, 1wt% yttrium oxide, 3% triethyl phosphate, and 10wt% organic solvent (ethanol:ethyl acetate=7:3) were ball-milled at 300rpm for 12h at 25°C to prepare a slurry; 8wt% binder (B72: B90 = 1: 1.5), 7.8wt% plasticizer (dibutyl phthalate: PEG600 = 1: 1), 0.2wt% BYK-1790 defoamer, and 18wt% organic solvent (ethanol: ethyl acetate = 7: 3) were stirred in a high-speed stirrer at 25°C and 300rpm for 2h to prepare a sol; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, the silicon nitride casting slurry C was poured into the casting tank, and the scraper height was set to 1.5 mm, the casting speed was 50 mm / min, and the drying temperature was 45° C. Finally, the silicon nitride casting green body was obtained.
[0064] Example 6 Example 6 is substantially the same as Example 5, except that the first adhesive is B74 (purchased from Eastman, with a molecular weight of 120K-150K and a hydroxyl content of 17.5%-20%), and the second adhesive is B79 (purchased from Eastman, with a molecular weight of 50K-80K and a hydroxyl content of 11%-13%).
[0065] Example 7 Example 7 is substantially the same as Example 5, except that the first adhesive is B60H (purchased from Kuraray, with a molecular weight of 150K-170K and a hydroxyl content of 18%-21%), and the second adhesive is B3OH (purchased from Kuraray, with a molecular weight of 60K-90K and a hydroxyl content of 18%-21%).
[0066] Comparative Example 1 (Low Molecular Weight PVB) A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 48.5wt% silicon nitride powder, 1.5wt% magnesium oxide, 1wt% yttrium oxide, 1wt% polyvinyl pyrrolidone, 26wt% ethanol and 11wt% ethyl acetate were ball-milled at 25°C and 300rpm for 12h to prepare a slurry; 6.5 wt % B98 PVB binder, 4 wt % triethylene glycol diisooctanoate, and 0.5 wt % BYK-1790 defoamer were added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, pour the silicon nitride casting slurry C into the casting tank, set the scraper height to 1.5 mm, casting speed to 50 mm / min, and drying temperature to 40-55°C; finally, obtain the silicon nitride casting green embryo. Figure 3 .
[0067] Comparative Example 2 (High Molecular Weight PVB) A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 48.5wt% silicon nitride powder, 1.5wt% magnesium oxide, 1wt% yttrium oxide, 1wt% polyvinyl pyrrolidone, 26wt% ethanol and 11wt% ethyl acetate were ball-milled at 25°C and 300rpm for 12h to prepare a slurry; 6.5 wt% B72 PVB binder, 4 wt% triethylene glycol diisooctanoate, and 0.5 wt% BYK-1790 defoamer were added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, pour the silicon nitride casting slurry C into the casting tank, set the scraper height to 1.5 mm, casting speed to 50 mm / min, and drying temperature to 40-55°C; finally, obtain the silicon nitride casting green embryo. Figure 4 .
[0068] Comparative Example 3 (Polymer PVB + Sol) A silicon nitride tape casting green body and a preparation method thereof, comprising the following steps: 48.5wt% silicon nitride powder, 1.5wt% magnesium oxide, 1wt% yttrium oxide, 1wt% polyvinyl pyrrolidone, 13wt% ethanol and 5.5wt% ethyl acetate were ball-milled at 25°C and 300rpm for 12h to prepare a slurry; 6.5wt% B72 PVB binder, 3.75wt% polyethylene glycol 600, 3.75wt% dibutyl phthalate, 0.5wt% BYK-1790 defoamer, 13wt% ethanol and 5.5wt% ethyl acetate were stirred in a high-speed mixer at 25°C and 300rpm for 2h to prepare a sol; The sol was added to the slurry and ball-milled at 300 rpm for 12 h at 25° C. to obtain slurry C; After vacuum degassing, pour the silicon nitride casting slurry C into the casting tank, set the scraper height to 1.5 mm, casting speed to 50 mm / min, and drying temperature to 40-55°C; finally, obtain the silicon nitride casting green embryo. Figure 6 .
[0069] Performance Testing Viscosity test: GB / T10247-2008 viscosity test method; Cast film thickness test: Use a vernier caliper to measure the thickness at four points on the cast film and calculate the average value; Cast film integrity test: Observe the cast film on site to see if there is peeling, cracking or agglomerated particles.
[0070] Test process: The size of the cast sheet is 240×190 mm. Determine whether there are defects based on the appearance of the cast sheet, for example, peeling, cracking or agglomerated particles on the surface of the sample. The performance test results are shown in Table 1.
[0071] Table 1. Performance test results:
[0072] Result Analysis Example 1: Combination Figure 1 The test results in Table 1 show that the silicon nitride casting slurry of Example 1 has good fluidity, the surface of the green embryo is flat and has no obvious defects, and can be easily demolded. In this solution, two common plasticizers, polyethylene glycol and dibutyl phthalate, are used, which are low in price and suitable for large-scale production.
[0073] Example 2: Figure 2 The silicon nitride slurry has good fluidity, the surface of the cast green body is flat and the thickness is uniform, and there are no obvious defects in appearance. The solvent is composed of non-toxic and low-cost ethanol and ethyl acetate, and the plasticizer uses environmentally friendly triethylene glycol diisooctanoate to replace phthalates to achieve an environmentally friendly formula.
[0074] Example 3: Changing the amount of powder, solvent and binder added. The silicon nitride slurry has good fluidity, the surface of the cast green body is flat and the thickness is uniform, and there are no obvious defects in appearance. The solvent is composed of non-toxic and low-cost ethanol and ethyl acetate, and the plasticizer uses environmentally friendly triethylene glycol diisooctanoate instead of phthalates to achieve an environmentally friendly formula.
[0075] Example 4: The solid content of silicon nitride powder is increased, the slurry has good fluidity, the surface of the cast green body is smooth and the thickness is uniform, and there is no obvious defect in appearance.
[0076] Example 5: Changing the amount of powder, solvent and binder added, the surface of the cast green body is flat and the thickness is uniform, there is no obvious defect in the appearance, and it can be easily demoulded; Example 6: Eastman B74 and B79 binders are used for compounding. The silicon nitride slurry has good fluidity, the surface of the cast green body is flat and the thickness is uniform, there are no obvious defects in the appearance, and it can be easily demolded; Example 7: Kuraray B60H and B30H are compounded. The silicon nitride slurry has good fluidity, the surface of the cast green body is flat and the thickness is uniform, there is no obvious defect in the appearance, and it can be easily demolded; Comparative Example 1: It is basically the same as Example 2, except that B98 low molecular weight binder is used, and the viscosity of the system is significantly reduced. Figure 3 , fine cracks appeared on the surface after tape casting, indicating that the binder could not completely wrap the powder.
[0077] Comparative Example 2: The same as Example 2, except that the B72 high molecular weight binder is used. The overall viscosity of the slurry is not high because a large amount of binder wraps around the grinding balls and cannot be dissolved in the system. Figure 4 , the cast film cracks seriously.
[0078] Comparative Example 3: It is basically the same as Example 1, except that the sol solution is prepared with high molecular weight PVB, the viscosity of the slurry system increases, and the tape casting operation is difficult. Figure 5 The slurry has poor fluidity and cannot fill the surface depressions during the molding process, resulting in defects.
[0079] Based on the above experimental results, it can be seen that the compound binder and presol process of the present invention can reduce the appearance defects of the casting and improve the yield of the casting.
[0080] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0081] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A binder for silicon nitride tape casting green body, characterized in that: include: The first binder and the second binder, wherein the weight average molecular weight of the first binder satisfies: (120-250)×10 3 The weight average molecular weight of the second binder satisfies: (25-90)×10 3 ; The weight ratio of the first binder to the second binder is 1:1-2.
5.
2. The binder for silicon nitride tape casting green body according to claim 1, characterized in that: The hydroxyl content in the first binder is 17.5% to 21%; the hydroxyl content in the second binder is 11% to 23%.
3. The binder for silicon nitride tape casting green body according to claim 1, characterized in that: The first binder and / or the second binder is polyvinyl butyral.
4. A silicon nitride tape casting green body, characterized in that: In terms of mass percentage, it includes: 45% to 55% silicon nitride powder, 1% to 3% sintering aid, 0.5% to 3% dispersant, 4% to 8% binder, 2.5% to 8% plasticizer, 0.2% to 0.5% defoamer and 25% to 45% organic solvent; Wherein, the binder is the binder for silicon nitride tape casting green body according to any one of claims 1 to 3.
5. The silicon nitride tape casting green body according to claim 4, characterized in that: The silicon nitride powder includes an α phase and a β phase, wherein the content of the α phase is w in mass percentage, wherein the w satisfies: w>90%.
6. The silicon nitride tape casting green body according to claim 4, characterized in that: The grain size of the silicon nitride powder satisfies: D50<1um; and / or, The specific surface area of the silicon nitride powder is m, wherein m satisfies: 10m 2 / g≤m≤20m 2 / g.
7. The silicon nitride tape casting green body according to claim 4, characterized in that: The sintering aid comprises magnesium oxide and / or yttrium oxide; and / or, The grain size of the sintering aid satisfies: D50<2um.
8. The silicon nitride tape casting green body according to claim 4, characterized in that: The dispersant includes at least one of polyvinyl pyrrolidone, triethyl phosphate and castor oil.
9. The silicon nitride tape casting green body according to claim 4, characterized in that: The organic solvent is a binary solvent system of a first organic solvent and a second organic solvent, and the weight ratio of the first organic solvent to the second organic solvent satisfies: 4:6-7:3; Preferably, the first organic solvent is ethanol, and the second organic solvent is ethyl acetate and / or butyl acetate.
10. The silicon nitride tape casting green body according to claim 4, characterized in that: The plasticizer includes at least one of dimethyl phthalate, dibutyl phthalate, dioctyl phthalate, polyethylene glycol and triethylene glycol diisooctanoate.
11. The silicon nitride tape casting green body according to claim 4, characterized in that: The defoamer includes at least one of a polyether defoamer, a silicone defoamer and a silicon-free defoamer.
12. A method for preparing a silicon nitride tape-casting green body, characterized in that: include: Prepare slurry: weigh 45% to 55% of silicon nitride powder, 1% to 3% of sintering aid, 0.5% to 3% of dispersant and 10% to 20% of organic solvent based on the mass percentage of each component in the slurry, mix them to obtain slurry; Preparation of sol: Based on the mass percentage of each component in the sol, weigh 4% to 8% of a binder, 2.5% to 8% of a plasticizer, 0.2% to 0.5% of a defoamer and 15% to 25% of an organic solvent, and stir and mix to obtain a sol; Preparing silicon nitride tape casting slurry: mixing the sol and the slurry to prepare silicon nitride tape casting slurry; Tape casting: The silicon nitride tape casting slurry is tape cast to obtain a silicon nitride tape casting green body.
13. The preparation method according to claim 12, characterized in that: The slurry preparation step: the components are fully mixed by ball milling, the mixing temperature is 20°C to 30°C, the mixing speed is 200rpm to 300rpm, the mixing method is ball milling, and the ball milling time is 10h to 24h; and / or, Preparation of sol step: controlling the stirring temperature to 20°C to 30°C, the stirring speed to 200rpm to 400rpm, and the stirring time to 2h to 5h; and / or, The steps of preparing silicon nitride tape casting slurry are as follows: the temperature of the tape casting is 20° C. to 30° C., the speed of the tape casting is 200 rpm to 300 rpm, and the time of the tape casting is 10 h to 24 h; Tape casting steps: set the scraper height to 1.0 mm to 1.5 mm, the tape casting speed to 50 mm / min to 100 mm / min, and the drying temperature to 40° C. to 55° C.; finally, a silicon nitride tape casting green body with a thickness of 0.40 mm to 0.65 mm is obtained.
14. A ceramic sheet, characterized in that: The ceramic sheet is manufactured by sintering the silicon nitride tape-cast green body according to any one of claims 4 to 11, or by sintering the silicon nitride tape-cast green body obtained by the preparation method according to claim 12 or 13.
15. Use of the ceramic sheet according to claim 14, characterized in that: The ceramic sheet is applied to substrate materials of power devices.